Diversidade de espécies no subgênero Micoureus Lesson, 1842 e o status taxonômico de Marmosa (Micoureus) constantiae Thomas, 1904 (Didelphimorphia, Didelphidae) - Silva, Luan Gabriel de Lima (2018)
The subgenus Micoureus Lesson, 1842 presents a wide geographic distribution from the south of Belize, in Central America, to the north of Argentina. It is comprised of six species and includes didelphidae marsupials with body mass between 35 and 144 g, facial mask, generally woolly fur that extends onto the base of the tail, and tail usually depigmented distally. Among these species, Marmosa constantiae Thomas, 1904 has never been revised, resulting in difficulties of establishing taxonomic and geographic limits for the species. This study aims to review M. constantiae based on morphological, morphometric and molecular analyzes. External and cranial morphology of 714 specimens deposited in several national and international zoological collections belonging to five species were examined. Genetic analyzes were performed using the mitochondrial molecular marker Cytochrome b (Citb) through genetic distance, Molecular Variance Analysis (AMOVA), Bayesian Inference, Maximum Likelihood and the General Mixed Yule Coalescent (GMYC) species delimitation analysis. The patterns of morphometric variation between M. constantiae and other allied species were evaluated through Principal Component Analysis and Discriminant Analysis. Based on our data set, it was possible to recognize M. constantiae as polyphyletic, composed of two lineages: one associated with Marmosa budini Thomas, 1920, with distribution in Paraguay, Argentina, south central Bolivia and west of Mato Grosso do Sul; and another associated with the Marmosa constantiae Thomas, 1904 (strict sensu) composed of five populations highly structured genetically, with distribution that includes eastern Peru, Bolivia and Brazil (Amazonas, Acre, Rondônia and western Mato Grosso). The morphometric and morphological analyzes corroborated with the molecular results, showing that both are morphometrically distinct and morphologically diagnosable – the first one is morphologically differentiated by the smaller body size, arrangement and presence of hairs on the tail, continuous cingulum on the lingual side of upper molars, cingulids on the labial side of lower molars, and the presence of palatine fenestrae. The result of the GMYC analysis indicates that the diversity of the subgenus may be five times greater than that currently recognized, especially M. demerarae, a taxon with the highest number of supposed species, phylogeographically structured. This study is the first one to infer the diversity within the subgenus Micoureus using integrated morphology, morphometry and molecular data and to review M. constantiae, demonstrating limited knowledge about the subgenus. Future studies involving morphological analyzes with all species and more molecular markers are necessary to describe the real diversity of Micoureus species.